Peningkatan Hasil Produksi, Penguatan Pemasaran Pada UKM Mak “Plengeh” Kediri - Sri Andayani; Nekky Rahmiyati; Endang Indartuti (JPM: Jurnal Pengabdian Masyarakat, 2021)
The impact of the Covid 19 virus has a profound effect on the national economy, including the presence of MSMEs. One of the smes affected in east Java is ukm "Mak Plengeh" his company name UD Wahyu Jaya. The main products made are Mak Plengeh's typical dry sponge and banana chips of all variants and Sanghai beans. Number of Employees 15 People. Problem 1). Decrease in sales or marketing up to 80% per month during Pandemic 2). The low production capacity for banana chips products is only 30 kg per day, because the slicing of bananas and fried chips is still manual, while the product needed 150 kg per day. 3. Lack of employee skills in the field of business management. External solutions and targets: 1) Procurement of banana slicer machine for banana chips as much as 1 piece. 2) Training on the use of equipment and maintenance Training and mentoring Financial management and marketing strategy 3) Scientific Publications in scientific journals and journals resulting from community service. Method of implementation of Equipment Procurement gradually. Training and mentoring are conducted while employees work (Learning by doing). Results after the introduction of TTG banana slicer machine and training on the use of tools, and business management training, the sales and marketing gradually increased.